The Effects of Pilot Structure on the Lean Ignition Characteristics of the Internally Staged Combustor - Zhengyan Guo; Yan Lu; Jingtao Yuan; Pimin Chen; Qibin Zhang; Wei Fan (Energies)
In order to explore the influence of pilot structure on the lean ignition characteristics in a certain type of internally staged combustor, the current study was conducted on the effects of the auxiliary fuel nozzle diameter, the rotating direction of the pilot swirler, and the swirl number on the lean ignition fuel–gas ratio limit, combining numerical simulation and experimental validation. The optimization potential of the mixing structure of this type of internally staged combustor was further explored. It indicated that the lean ignition fuel–gas ratio limit was significantly influenced by the diameter of the auxiliary fuel nozzles the swirl number of the pilot swirler and the combination of the same rotating direction for both pilot swirlers, while the mass flow rate of air was constant. Increasing the diameter of the auxiliary fuel path nozzles (0.4~0.6 mm) and having excessively higher or lower swirl numbers of the pilot module primary swirlers are not conducive to broadening the lean ignition boundary. Compared with the two-stage pilot swirler with the same rotation combination, the fuel–gas ignition performance of the two-stage pilot swirler with the opposite rotation combination is better. Under the typical working conditions (the air mass flow rate is 46.7 g/s and the ignition energy is 4 J), for a pilot swirler with a rotating direction opposite to the main swirler, the diameter of the auxiliary fuel nozzles is 0.2 mm, the swirl number of first-stage of pilot swirler is 1.4, and the lean ignition fuel–air ratio was reduced to 0.0121, which is 32.78% lower than the baseline scheme, which further broadens the lean ignition boundary of the centrally staged combustion chamber.